Penerapan Active Cycle of Breathing Technique pada Pasien dengan Hemoptisis Post Tuberculosis: Studi Kasus - Sihombing, Yulia; Priscalini Dano, Cindy; Naomi Marchilia Da Costa, Audrey; Nalle, Yohana (Pustaka Galeri Mandiri, 2025)
Background: Hemoptysis is coughing up blood originating from the lungs or tracheobronchial tract, which can be found in patients with active or inactive tuberculosis (TB) infection. Untreated hemoptysis can lead to hypovolemic shock, atelectasis, asphyxia, anemia, and even death due to sputum retention, which causes airway obstruction and impairs airway patency. One intervention that can be given to keep the patient's airway patent is the active cycle of breathing technique (ACBT). ACBT is an airway clearance technique with the ultimate goal of increasing lung expansion and sputum removal, thus reducing airway obstruction. Objective: to determine the effect of applying the active cycle of breathing technique (ACBT) on the removal of retained secretions and increased lung expansion. Method: The method used in this study was a case study of one patient with haemoptysis and a history of post-TB who was treated in the ward. Monitoring was conducted before and after intervention for three days using the following instruments: vital signs (respiratory rate, oxygen saturation), coughing ability and sputum production, airway patency, breath sounds, and patient complaints. The results: After the intervention, coughing decreased, sputum output increased, physiological parameters such as respiratory rate and oxygen saturation improved, and patient comfort increased. Discussion: ACBT is effective as an intervention in maintaining airway clearance in patients with haemoptysis who are treated in the inpatient ward.